Influence of electrode profiles on electrical discharge machining of titanium - Zain, Zakaria Mohd; Khan, Ahsan Ali; Abdulkareem, Suleiman (Trans Tech Publications, 2011)
Electric discharge machining (EDM) is an effective manufacturing technique that enables the production of parts made of hard materials with complicated geometry that are difficult to produce by conventional machining processes. EDM is a process of eroding material by transient action of electric sparks on electrically conductive materials, one being the workpiece the other being the electrode immersed in a dielectric fluid and separated by a spark gap. The EDM ability to control the process parameters to achieve the required dimensional accuracy and surface finish has placed this machining operation in a prominent position in industrial applications. This work reports on the different electrode profiles on the machinability factors of surface roughness (Ra) and material removal rate (MRR). The machining factors used in this study are the current (I), on-time and off-time. Based on the experimental